(untitled) (Third Sector Social Economic Review, 2020)
This study aims to unveil the bibliometric characteristics of master’s and doctoral theses in Marketing Discipline including the years between 2010 and 2020 in terms of various parameters. This study also aims to reveal the general characteristics of marketing literature and provide convenience for the researchers of this field. For this purpose, the graduate theses were reviewed with regards to some bibliometric characteristics (such as type of thesis, release year, university released, the topic of thesis, research method, data type, data collection method, analysis technique, scale type, population, sampling method, sampling size, publication status, number of citations). Content analysis method was used in the study and 558 theses were investigated to reveal the characteristics of current knowledge. The findings indicated that almost all the theses were empirical and these empirical studies used quantitative research methods more than qualitative and mixed research methods. The primary data were the most used data type, which was mainly collected from “consumers” via “convenience sampling” by “survey”. The results presented that “Consumer Behavior”, “Brand and Brand Management” and “Marketing Communication” are the most frequently studied subjects. In addition, it is determined that research hypotheses and models are involved in most of the theses. While “Factor Analysis” and “Analysis of Variance (ANOVA)” are the most used analysis techniques; Likert Type Scale is the primary scale type. On the other hand, it is worth noting that more than half of the theses do not have pre-test finding and the theses mainly refer to the foreign literature sources. Finally, it is also worth noting that only a very limited number of the theses turned into an academic paper, and the number of citations was relatively low. This study contributes to the literature by comprehensively revealing the characteristics of Marketing theses and shedding light on the future research direction.